Warming and leaf litter functional diversity, not litter quality, drive decomposition in a freshwater ecosystem - Migliorini, Gustavo H. [UNESP]; Romero, Gustavo Q. (Nature Research, 2020)
Environment, litter composition and decomposer community are known to be the main drivers of litter decomposition in aquatic ecosystems. However, it remains unclear whether litter quality or functional diversity prevails under warming conditions. Using tank bromeliad ecosystems, we evaluated the combined effects of warming, litter quality and litter functional diversity on the decomposition process. We also assessed the contribution of macroinvertebrates and microorganisms in explaining litter decomposition patterns using litter bags made with different mesh sizes. Our results showed that litter decomposition was driven by litter functional diversity and was increasingly higher under warming, in both mesh sizes. Decomposition was explained by increasing litter dissimilarities in C and N. Our results highlight the importance of considering different aspects of litter characteristics (e.g., quality and functional diversity) in order to predict the decomposition process in freshwater ecosystems. Considering the joint effect of warming and litter traits aspects allow a more refined understanding of the underlying mechanisms of climate change and biodiversity shifts effects on ecosystem functioning.